Challenges faced by older nurses in Singapore: a mixed methods study. (17th January 2017) - Ang, S.Y.; Ayoob, S.B.M.; Hussain, N.B.S.; Uthaman, T.; Adenan, H.; Chiang, P.; Ong, L.T.; Fong, M.K.; Ostbye, T.
Abstract : Background: In Singapore, employees aged 62–65 can continue to be employed if they meet the re‐employment eligibility criteria. This policy, coupled with an ageing workforce, calls for age‐friendly initiatives, specific to work‐related challenges faced by older nurses. Aim: To determine work‐related challenges faced by older nurses. Methods: A mixed method sequential explanatory study was conducted with nurses, aged 50 and above, working in a healthcare cluster in Singapore. In the quantitative phase, a questionnaire was administered to 534 nurses to elicit work‐related challenges, then in‐depth interviews with 30 nurses were carried out to help explain why certain tasks and work circumstances became harder. Results: Results of the survey indicated that the top three challenges were coping with changes, working with computers and reading labels. Place of work, salary range, gender and race were significantly associated with different work‐related challenges. Five themes emerged from the qualitative data: physical demands of work and workload, new technology, need for further education, working with younger nurses and in intercultural teams, and changing public expectations and professional image. Discussion and conclusion: The study supports the current literature on the challenges older nurses face with technological advancement. However, older nurses in our study reported less aches and pain as compared to that reported elsewhere. There is a need for specific strategies that will address changes in work processes and environment in order to retain older nurses. Implications for nursing and nursing policy: When devising age‐friendly work improvement initiatives, it is important for nurse leaders to factor in the needs of nurses working in different care environments, who are of different ranks, or are from different ethnic backgrounds.